2023
DOI: 10.3390/polym15030670
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Degradation of Poly-ε-caprolactone Composite Scaffolds for Large Bone Defects

Abstract: This research investigates the accelerated hydrolytic degradation process of both anatomically designed bone scaffolds with a pore size gradient and a rectangular shape (biomimetically designed scaffolds or bone bricks). The effect of material composition is investigated considering poly-ε-caprolactone (PCL) as the main scaffold material, reinforced with ceramics such as hydroxyapatite (HA), β-tricalcium phosphate (TCP) and bioglass at a concentration of 20 wt%. In the case of rectangular scaffolds, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The results showed that PCL/Bioglass exhibited higher degradation kinetics than PCL, PCL/HA, and PCL/TCP. Additionally, the degradation processes increased with increasing pore size [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that PCL/Bioglass exhibited higher degradation kinetics than PCL, PCL/HA, and PCL/TCP. Additionally, the degradation processes increased with increasing pore size [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 , scaffolds with a 0°/90° lay-down pattern architecture, 330 μm fibre diameter, and 350 μm top view and 210 μm side view pore size, were fabricated using 3D Discovery (regenHU, Switzerland), a screw-assisted material-extrusion additive manufacturing system, at room temperature and with the optimal processing parameters previously reported (nozzle diameter of 330 μm, printing temperature of 90 °C, air pressure of 6 bars, deposition velocity of 13 mm/s, and screw rotational velocity of 8 rpm, and layer thickness of 270 μm) [ [40] , [41] , [42] ]. The geometrical characteristics of the considered scaffolds were based on previous studies from our group that investigated the effect of filament diameter, pore size, and porosity on mechanical and biological properties [ [42] , [43] , [44] , [45] ]. As reported the considered values are the ones that allow both high mechanical properties and cell attachment, proliferation, and differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that. The degradation kinetics of PCL/ BG bone scaffold was enhanced when the pore size increased from 500 μm to 200 μm [11] . Degradable scaffolds can release chemicals to stimulate cell growth and differentiation during degradation, thereby promoting tissue regeneration.…”
Section: Bioglassmentioning
confidence: 99%
“…[9] Qiao Yongjie, Zhang Lvdan, Li Xusheng, et al β-tricalcium phosphate filled with drug-loaded microspheres for the treatment of infectious bone defects in rabbits [J]. Orthopedic Journal of China, 2021, 29 (11):1013-1018.…”
Section: Referencesmentioning
confidence: 99%